2022
DOI: 10.3390/app12062954
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference-Based Pesticides and Antiviral Agents: Microbial Overproduction Systems for Double-Stranded RNA for Applications in Agriculture and Aquaculture

Abstract: RNA interference (RNAi)-based pesticides are pest control agents that use RNAi mechanisms as the basis of their action. They are regarded as environmentally friendly and are a promising alternative to conventional chemical pesticides. The effective substance in RNAi-based pesticides is double-stranded RNA (dsRNA) designed to match the nucleotide sequence of a target essential gene of the pest of concern. When taken up by the pest, this exerts an RNAi effect and inhibits some vital biochemical/biological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 116 publications
0
8
0
2
Order By: Relevance
“…This paper highlights the potential dsRNA target genes in aquatic pathogens that can reduce pathogen infection and improve the survival of aquatic host animals after silencing and also introduces species used as feed for oral-based dsRNA, such as E. coli and microalgae. An increasing number of studies has shown that the use of E. coli is a very inexpensive way to synthesize dsRNA, and E. coli is constantly being modified to obtain high yields ( Hashiro and Yasueda, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This paper highlights the potential dsRNA target genes in aquatic pathogens that can reduce pathogen infection and improve the survival of aquatic host animals after silencing and also introduces species used as feed for oral-based dsRNA, such as E. coli and microalgae. An increasing number of studies has shown that the use of E. coli is a very inexpensive way to synthesize dsRNA, and E. coli is constantly being modified to obtain high yields ( Hashiro and Yasueda, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Created with BioRender.com. et al 10.3389/ffunb.2022.977502 et al, 2019Islam et al, 2021;Hashiro and Yasueda, 2022). Indeed, the development of microbial-based dsRNA production systems has reduced the price of dsRNAs from ~US$ 12,000/g in 2008, to US$ 1/g, with Greenlight's GreenWorXTM system aiming to further lower the price of dsRNA synthesis to around US$ 0.5/g (reviewed in Guan et al, 2021).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…dsRNA can be produced using either in vitro transcription or in vivo expression in bacteria, yeast, microalgae and other species [130][131][132][133][134]. Bacteria are a low-cost alternative for the production of large amounts of dsRNA [135]. Escherichia coli HT115 (DE3) were first used as an heterologous dsRNA production system by [136].…”
Section: Dsrna Productionmentioning
confidence: 99%